Hybrid GMP–polyamine hydrogels as new biocompatible materials for drug encapsulation. Issue 28 (29th June 2020) - Lopera, Alberto; Aguilar, Juan A.; Belda, Raquel; Verdejo, Begoña; Steed, Jonathan W.; García-España, Enrique
Abstract : Pyrazole-based polyamines stabilise G-quartet based GMP hydrogels at human skin pH and GMP concentrations one order of magnitude lower than typically employed, allowing in some cases drug encapsulation without disrupting the hydrogel structure. Abstract : Here we present the preparation and characterization of new biocompatible materials for drug encapsulation. These new gels are based on positively charged [1+1] 1 H -pyrazole-based azamacrocycles which minimise the electrostatic repulsions between the negatively charged GMP molecules. Rheological measurements confirm the electroneutral hydrogel structure as the most stable for all the GMP–polyamine systems. Nuclear magnetic resonance (NMR) was employed to investigate the kinetics of the hydrogel formation and cryo-scanning electron microscopy (cryo-SEM) was used to obtain information about the hydrogel morphology, which exhibited a non-homogeneous structure with a high degree of cross-linking. It is possible to introduce isoniazid, which is the most employed antibiotic for tuberculosis treatment, into the hydrogels without disrupting the hydrogel structure at appropriate concentrations for oral administration.